2020
DOI: 10.3889/oamjms.2020.5177
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation Dan Hygiene Analysis, and Individual Factors for Stunting among Children Under Two Years in Ambon

Abstract: BACKGROUND: Nutrition problem is a problem that is still a threat in various countries around the world, one of which is stunting that occurs since the baby is in the womb and in the early period after the baby is born, but only appears after the child is 2 years old. AIM: This study aimed to analyze the water, sanitation and hygiene (WASH), and individual factors for the incidence of stunting in children aged 7–24 months in the slums of Ambon City. METHODS: The research was an analytical observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
(19 reference statements)
0
4
1
9
Order By: Relevance
“…Namun, hasil penelitian ini menunjukkan bahwa tidak ada korelasi antara tingkat pendidikan ibu dengan kejadian stunting (Tabel 1). Penelitian sebelumnya juga menemukan hal serupa 35,49,50,51 . Hal ini diduga karena sebagian besar responden, baik yang memiliki balita stunting ataupun tidak stunting, berada pada kondisi dengan strata pendidikan yang sama.…”
Section: Hasil Dan Pembahasanunclassified
“…Namun, hasil penelitian ini menunjukkan bahwa tidak ada korelasi antara tingkat pendidikan ibu dengan kejadian stunting (Tabel 1). Penelitian sebelumnya juga menemukan hal serupa 35,49,50,51 . Hal ini diduga karena sebagian besar responden, baik yang memiliki balita stunting ataupun tidak stunting, berada pada kondisi dengan strata pendidikan yang sama.…”
Section: Hasil Dan Pembahasanunclassified
“…The number of deaths due to diarrhea is 1.8 million people every year. Previous study in Ambon [32] explained that water, sanitation and hygiene (WASH), and low birth weight status are the risk factors of stunting for the children aged 7-26 months.…”
Section: Clean and Healthy Life Behaviourmentioning
confidence: 99%
“…Smoking behavior affects the health and nutritional status of the family, as the research [32] stated that cigarette smoke from the smoking parent has a direct impact on the children's growth and development Int J Public Health Sci ISSN: 2252-8806  by disturbing the nutrition absorption to the children. This result is supported by a previous study conducted by Semba et al [33] which found that tobacco used by parents was the risk factor for malnutrition in children living in poor families in an urban area, Indonesia.…”
Section: Clean and Healthy Life Behaviourmentioning
confidence: 99%
“…Penyebab lain berupa kurangnya pengetahuan masyarakat sehingga banyak terjadinya pernikahan dini, kurangnya pengetahuan ibu mengenai pemberian MPASI yang tepat, ibu balita kurang memberikan asupan makanan yang bergizi untuk anaknya dan juga ibu pada saat hamil (Choirina, 2021;Nengsih et al, 2016). Seorang anak dapat dikatakan mengalami stunting dengan membandingkan tinggi seorang anak dengan standar tinggi anak pada populasi normal yang sesuai dengan usia dan jenis kelamin yang sama, yaitu berada dibawah 2 SD (Dhok & Thakre, 2016;Hasanah et al, 2020).…”
Section: Pendahuluanunclassified